Post HIPC relief impact on the economic development of the Gambia - TRAWALLY, Lamin (KDI School, 2017)
The Heavily Indebted Poor Countries (HIPC) Initiative was launched in 1996 and was further enhanced in 1999 by the International Financial Institutions (IFIs) with the objective of providing debt relief to poor countries. The Gambia has benefited from the HIPC initiative, which comprises debt relief or debt cancellation from International Development Association (IDA), African Development Bank (AFDB) and the European Union (EU). The Gambia qualify for HIPC relief from the year 2000 which is regarded as the decision point, through 2007 which is regarded as the HIPC relief completion point. The main aim of the relief was to create fiscal space through the reduction of the debt burden to a sustainable level. In the case of the Gambia, the fiscal space created by debt relief has been utilized by Government to increase its spending on poverty-reducing expenditures like education and healthcare. Given the overall objective of HIPC relief initiative, which is to create fiscal space, increase growth and to alleviate poverty, this paper, therefore, intends to specifically analyze in detail the post HIPC relief impact on the economic development of the Gambia. The results indicated that HIPC relief together with its conditionalities has led to economic development in the Gambia. Effective implementation of prior actions to benefiting from the HIPC relief (HIPC conditionalities) leads to a sound macroeconomic stability and good governance in the country. There has also been an increase spending on poverty-reducing expenditures thereby improving the education and health sectors respectively. Improvement in health and education sectors have undoubtedly improved the leaving conditions of the citizens thereby reducing poverty to some degree which however has not been statistically very significant.
Thesis(Master) --KDI School:Master of Public Policy,2017